Efek Pelembab Minyak Biji Bunga Matahari Dalam Sediaan Krim Tangan - Nurul Husna; Suryanto Suryanto*; Djendakita Purba (Journal of Pharmaceutics and Pharmacology, 2012)
Background: Sunflower seed oil contains mainly of triacylglycerols (98–99%), and a small fraction of phospholipids, tocopherols, sterols, and waxes. The content is that causes oleum helianthi to be used as an emollient in skin care massage. Objective: This study was carried out to investigate the moisturizing effect of sunflower seed oil for skin. Methods: Hand cream preparations were prepared by using some components such as stearic acid, cetyl alcohol, triethanolamine, methylparaben, butylated hydroxytoluene, oleum rosae, distilled water, and adding sunflower seed oil at the concentration of 10, 12, 14, 16, and 18% as well as blank. The tests were done to evaluate the ability of the preparations to reduce the evaporation of water from the skin. The data obtained was analyzed statistically using ANOVA with confidence level of 95%. Result: The preparation contained sunflower seed oil at the concentration of 10, 12, 14, 16, and 18% had ability to reduce the evaporation of water from the skin of 26.84, 34.16, 40.68, 45.88, and 52.32%, respectively. Statistical analysis using ANOVA with confidence level of 95% showed that the ability of the preparations to reduce the evaporation of water from the skin were significantly difference. Conclusion: Sunflower seed oil has moisturizer effect for skin in hand cream preparation. Keywords: sunflower seed oil, cream, moisturizer, skin ABSTRAK Latar belakang: Minyak biji bunga matahari memiliki kandungan utama berupa triasilgliserol (98-99%), dan sebagian kecil berupa fosfolipid, tokoferol, sterol, dan lilin. Kandungan inilah yang menyebabkan minyak biji bunga matahari digunakan sebagai emolien dalam pijat perawatan kulit. Tujuan: Penelitian ini dilakukan untuk menguji efek pelembab minyak biji bunga matahari terhadap kulit. Metode: Sediaan krim tangan dibuat dengan beberapa komponen, di antaranya asam stearat, setil alkohol, trietanolamin, metil paraben, butilhidroksitoluen, oleum rosae, air suling, dan penambahan minyak biji bunga matahari dengan konsentrasi 10, 12, 14, 16, dan 18% serta blanko. Pengujian dilakukan untuk menentukan kemampuan sediaan dalam mengurangi penguapan air dari kulit. Data yang diperoleh dianalisis secara statistik menggunakan metode analisis varians (ANAVA) dengan taraf kepercayaan yang digunakan adalah 95%. Hasil: Sediaan yang mengandung minyak biji matahari dengan konsentrasi 10, 12, 14, 16, dan 18% mampu mengurangi penguapan air dari kulit masing-masing sebesar 26,84; 33,89%; 40,95; 45,88; dan 52,32%. Analisis statistik menggunakan ANAVA dengan taraf kepercayaan 95% menunjukkan bahwa kemampuan masing-masing sediaan dalam mengurangi penguapan air dari kulit berbeda secara signifikan. Kesimpulan: Minyak biji bunga matahari memiliki efek pelembab terhadap kulit dalam sediaan krim tangan. Kata kunci: minyak biji bunga matahari, krim, pelembab, kulit *Korespondensi penulis: yanto_juni@ymail.com